Circulating miRNAs are associated with frailty and ST-elevation myocardial infarction pathways. (March 2023) - Ramos, Juan Thomaz Gabriel de Souza; Pereira, Amanda Gomes; Ferrari, Felipe Sanches; Andrade, Morganna Freitas; de Melo, Caroline Souto; Boas, Paulo José Fortes Villas; Felix, Tainara F.; de Carvalho, Marcio; Dorna, Mariana Souza; Azevedo, Paula Schmidt; Phillips, Bethan E.; Polegato, Bertha Furlan; et al.
Highligths: Frailty and ST-Elevation Myocardial Infarction (STEMI) share similar molecular pathways. The discovery of specific biomarkers, such as microRNAs, may provide insights into the molecular mechanisms of this relationship. Pre-frail/frail patients had greater serum levels of 53 miRNAs, compared with non-frail patients. miR-103a-3p, miR-598-3p, and miR-130a-3p were the top three miRNAs predicted to modulate gene expression associated with aging. Abstract: Background: Frailty and ST-Elevation Myocardial Infarction (STEMI) share similar molecular pathways. Specific biomarkers, such as microRNAs (miRNAs), may provide insights into the molecular mechanisms that cause the relationship between frailty and STEMI. Objective: Our aim was to identify and compare circulating miRNA levels between frail and non-frail older adults following STEMI and comprehend the regulatory miRNA-gene networks and pathways involved in this condition. Methods: This exploratory study is a subanalysis of a larger observational study. In this study, we selected patients ≥ 65 years old, following STEMI, with pre-frail/frail (n=5) and non-frail (n=4) phenotype evaluated using the Clinical Frailty Scale and serum circulating miRNA levels were analyzed. Results: Pre-frail/frail patients had greater serum levels of 53 miRNAs, compared with non-frail patients. Notably, miR-103a-3p, miR-598-3p, and miR-130a-3p were the top three significantly deregulated miRNAs predicted to modulate gene expression associated with aging. Additional computational analyses showed 7, 420 predicted miRNA gene targets, which were regulated by at least two of the 53 identified miRNAs. Pathway enrichment analysis showed that axon guidance and MAPK signaling were among pathways regulated by miRNA target genes. Conclusions: These novel findings suggest a correlation between the identified miRNAs, target genes, and pathways in pre-frail and frail patients with myocardial infarction.